Effect of Methyl Jasmonate, Sodium Selenate and Chitosan as Exogenous Elicitors on the Phenolic Compounds Profile of Broccoli Sprouts - Zuniga-Navarro, G; Mahn-Osses, A; Barrientos-Carvacho, H; Barrientos-Carvacho, H (John Wiley and Sons Ltd, 2014)
BACKGROUND: Broccoli sprouts are a good source of secondary metabolites, exhibiting biological activity, such as polyphenols, whose concentration is affected by the exposure to exogenous elicitors. The aim of this work was to investigate the effect of sodium selenate, chitosan and methyl jasmonate, applied directly to the seeds or through irrigation, on the content and profile of phenolic compounds in broccoli sprouts. The effect on antioxidant activity was also investigated. RESULTS: Methyl jasmonate and chitosan decreased antioxidant capacity. Methyl jasmonate significantly decreased total polyphenols content in comparison with control sprouts, while chitosan significantly increased it. Sodium selenate had no statistical effect on antioxidant capacity and total polyphenols concentration. The polyphenols profile in sprouts was composed by quercetin, morine, genisteine, luteoline and sinapic acid. Elicitor type and concentration affected the synthesis of these compounds. Chitosan stimulated the synthesis of quercetin, sinapic acid and morine, whereas methyl jasmonate stimulated the synthesis of luteoline. Sodium selenate had no effect on polyphenols synthesis. CONCLUSION: The exposure of broccoli to the elicitors produced changes in the phenolic compounds profile of broccoli sprouts. Besides, the stimulation of phenolic compounds synthesis was elicitor-specific, thus opening the possibility of managing culture conditions to increase the content of a specific phenolic compound. © 2014 Society of Chemical Industry.
Keywords: exogenous elicitor; phenolic compounds; antioxidant activity; broccoli sprouts